Reconstruction filter suitable for lowpass delta-sigma RF transmitters - Defu Wang; Renato Negra (2013 IEEE 13th Topical Meeting on Silicon Monolithic Integrated Circuits in RF Systems, 2013)
This paper proposes a highly selective bandpass filter suitable for lowpass delta-sigma RF transmitters. The proposed filter is characterized by a low insertion loss, high selectivity and a transfer function tailored for filtering the close-up out-of-band noise of lowpass delta-sigma transmitters. The circuit design is based on a modified stub-loaded ring resonator structure. The proposed filter has been implemented and the measurements show good agreement with simulation. The proposed filter provides a fractional 3-dB bandwidth of 14.6 %, an insertion loss of less than 1.3 dB, a suppression of more than 15 dB on both sides of desired band, and a sharp cut-off frequency response.